PENGARUH KOMITMEN ORGANISASI DAN PENGENDALIAN INTERNAL TERHADAP RESIKO TERJADINYA KECURANGAN (FRAUD) DALAM PELAKSANAAN JAMINAN KESEHATAN DI RUMAH SAKIT BHAYANGKARA TK. IV POLDA SULUT - Natasya, Toisuta Novenia; Karamoy, Herman; Lambey, Robert (Universitas Sam Ratulangi, 2017)
Fraud is an action that is often found in various organizations or agencies. By instilling a high sense of organizational commitment to each individual as well as the establishment and implementation of internal controls, it is hoped that it will create a barrier to the misuse by public servants, especially in the field of health such as doctors and other paramedics in the implementation of health insurance. This research was aimed to determine the risk of fraud in the implementation of health insurance. The population of this research is all employees who work in hospital Bhayangkara TK..IV Polda Sulut. This study used multiple linear regression method with the help of spss. The results of hypothesis shown that the organizational commitmentÂ has no significant impact on fraud risk. Internal control give the significant impact to the risk of fraud.Keywords: Fraud, Organizational Commitment, Internal Control